Interest Rate Defenses of Currency Pegs - Sole, Juan (IMF Working Papers; Working Paper ;, 2004)
This paper studies a policy often used to defend a currency peg: raising short-term interest rates. The rationale for this policy is to stem demand for foreign reserves. Yet, this mechanism is absent from most monetary models. This paper develops a general equilibrium model with asset market frictions where this policy can be effective. The friction I emphasize is the same as in Lucas (1990): money is required for asset transactions. When the government raises domestic interest rates, agents want to increase their holdings of domestic currency in order to acquire more domestic-currency-denominated assets. Thus, agents do not run on the reserves of the central bank, and the peg survives. A key implication of the model is that an interest rate defense can always be successful, but at great costs for domestic agents. Hence the reluctance of governments to sustain this policy for long periods of time.